UJI AKTIVITAS ENZIM PROTEASE DARI ISOLAT Bacillus sp. ENDOFIT TANAMAN KELAPA SAWIT (Elaeis quinensis) - Atika Marnolia; Yuli Haryani; Fifi Puspita (LPPM Universitas Muhammadiyah Riau, 2016)
Proteolytic bacteria are able to hydrolyze proteins into amino acid and smaller peptides. The objective of this study to determine the abilty of three Bacillus sp. isolated from leaf (BD), root (BA), and stem (BP) of palm oil to produce protease. The proteolytic activity was determine based on the amount of tyrosin liberated in Unit/mL, while the specific activity was indicated by activity per unit weight of proteins. Protein concentration of enzymes extracts was determined by Lowry method. The results showed that all isolates were able to produce protease. Protease activity of Bacillus sp. BD, BA and BP was (711,260 ± 0,735) x 10-3 U/mL, (708,536 ± 0,918) x 10-3 U/mL and (710,027 ± 0,091) x 10-3 U/mL in optimal production times of 24 hours, repectively.